Highly Oxidized States of Phthalocyaninato Terbium(III) Multiple‐Decker Complexes Showing Structural Deformations, Biradical Properties and Decreases in Magnetic Anisotropy. Issue 39 (18th June 2020) - Horii, Yoji; Damjanović, Marko; Ajayakumar, M. R.; Katoh, Keiichi; Kitagawa, Yasutaka; Chibotaru, Liviu; Ungur, Liviu; Mas‐Torrent, Marta; Wernsdorfer, Wolfgang; Breedlove, Brian K.; Enders, Markus; Veciana, Jaume; et al.
Abstract: Presented here is a comprehensive study of highly oxidized multiple‐decker complexes composed of Tb III and Cd II ions and two to five phthalocyaninato ligands, which are stabilized by electron‐donating n ‐butoxy groups. From X‐ray structural analyses, all the complexes become axially compressed upon ligand oxidation, resulting in bowl‐shaped distortions of the ligands. In addition, unusual coexistence of square antiprism and square prism geometries around metal ions was observed in +4 e charged species. From paramagnetic 1 H NMR studies on the resulting series of triple, quadruple and quintuple‐decker complexes, ligand oxidation leads to a decrease in the magnetic anisotropy, as predicted from theoretical calculations. Unusual paramagnetic shifts were observed in the spectra of the +2 e charged quadruple and quintuple‐decker complexes, indicating that those two species are actually unexpected triplet biradicals. Magnetic measurements revealed that the series of complexes show single‐molecule magnet properties, which are controlled by the multi‐step redox induced structural changes. Abstract : Stacking up : From extensive studies on highly oxidized species of phthalocyaninato‐lanthanoid‐cadmium multiple‐decker complexes, the complexes had staggered and eclipsed conformations and showed complicated changes in their magnetic anisotropies and biradical properties.